(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Objective: To find out the causes and pattern of traumatic rupture of tympanic membrane (TM) and their prognosis. Methods: This was a cross sectional study and carried out in the Department of Otolaryngology- Head & Neck Surgery, Tairunessa Memorial Medical College & Hospital, Boardbazar, Gazipur, in a period of 18 months from January 2011 to December 2013 among those had traumatic ruptured tympanic membrane attending in our hospital. 70 cases were taken and the data were collected by interviewing the cases as per questionnaire from history, examinations & investigation reports. Results: This study showed people of 21-30 years (65.5%) are mostly affected and males (36) were more affected than females (34) and housewives (34.5%) were commonest group of people. 88.5% of cases the cause of rupture is slapping and 42% cases slapped by her own husbands. From this study we got left ear was involved in (60)85%of cases. It needs 22-28 days in 57.14% of cases to heal the membrane. Almost all 94.5% of cases it heals spontaneously. Conclusion: It needs early diagnosis, no intervention and no entry of water. In most cases they heal spontaneously the ruptured TM Bangladesh J Otorhinolaryngol; April 2015; 21(1): 38-42